The Degree of Commitment of Physical Education Teachers in Applying the Curricula from the Perspective of Supervisors in the Central and North Regions - Yousef, Anas Ahmad (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the degree of commitment of physical education teachers in applying the physical education curriculum from the point of view of physical education supervisors in the central and northern regions. And the north according to the variable (experience in supervision، educational qualification, and the region), where the study sample consisted of (34) supervisors in the directorates of education in the regions (Central and North)، and the descriptive approach was used in the survey style, where the researcher designed a tool to measure the degree of commitment Physical education teachers in the application of the physical education curriculum from the point of view of physical education supervisors in the central and northern regions included (37) phrases distributed over (4) areas, and the results of the study indicated that the professional field related to the teacher obtained a large degree and the field of material capabilities and facilities came to a large extent Also, While the field of the curriculum teacher’s guide and the technical field related to the supervisor got a medium degree, and the results also showed that there were no statistically significant differences at the level of significance (0.05 ≥α) from the supervisors’ point of view attributed to the experience variable in supervision and the region, while the results indicated that there are differences between the arithmetic averages to the degree of commitment of physical education teachers in applying the physical education curriculum from the point of view of physical education supervisors in the central and northern regions due to the educational qualification variable, and in light of results of the study the researcher recommends, The necessity of rehabilitating physical education teachers professionally and academically to achieve the objectives of the curriculum before and during service, and to work on modifying and developing the physical education curriculum in proportion to the capabilities available in schools, and to increase the supervisory visits to physical education teachers and to involve them in continuous training courses.